Sustainability in Industry: The Lack of Implementation Running in the FMCG Industry - Daniel Susilo; Carlo Magno T. Mendoza; Mohammad Ali Khan (Jurnal Ekonomi dan Bisnis Digital, 2023)
The FMCG industry is an impactful industry in many regions, especially when it is running during the COVID-19 pandemic, and they still make progress. However, as good as its blessings are, the FMCG industry has its struggles with innovation, and each region has shown some differences until now; thus, the data speaks for itself. India, which has a Hindu majority, and their vegetarianism show some differences in how they explored the wisdom of the FMCG industry. It makes the industry unique on its own to have an eco-friendly movement through a cultural push of their vegetarian beliefs. The method was Krippendorf content analysis on Twitter, we’ll get closer to looking at the unique data. Findings have shown that changing consumer preferences have also impacted the FMCG industry in India. Consumers are becoming more health-conscious and opting for products that are natural, organic, and free from harmful chemicals.